Exploring the contours of consumer heterogeneity : Towards a typology of domestic hydrogen acceptance - Gordon, Joel A. ; 0000-0001-5000-5000; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Energy Research and Social Science, 2024)
Hydrogen energy technologies are anticipated to play a fundamental role in securing a decarbonised energy future. While the deployment of low-carbon hydrogen energy systems remains nascent and is subject to a range of techno-economic constraints, potential scalability will also hinge on social acceptance. In response, this study draws on extensive national survey data to derive a comprehensive typology of domestic acceptance, which reflects multiple factors influencing consumer attitudes towards low-carbon hydrogen heating and cooking appliances. The proposed typology is developed through rigorous coding of over 1000 qualitative statements, leading to 12 core acceptance factors composed of a mix of positive, neutral, and negative sub-factors. The study finds that eight primary sub-factors account for close to 60 % of identified codes, with knowledge deficit (negative), environmental benefits (positive), and financial risks (negative) ranking highest. Critically, these three sub-factors are also the most statistically significant predictors of consumer heterogeneity. At the sub-group level, the analysis shows that engagement with renewable energy technology and climate change is associated with stronger perceptions of environmental benefits and lower financial concerns. By contrast, perceived financial risks and concerns over energy injustice constrain acceptance levels among fuel stressed respondents. Through mixed-methods analysis, the study transmits the value of advancing acceptance typologies as a critical mechanism for enacting a ‘just’ hydrogen economy. The analysis supports developing strategic measures which account for consumer heterogeneity to better support socially acceptable pathways for residential decarbonisation.
Publisher Copyright: © 2023 The Authors
Keywords: Domestic hydrogen; Energy justice; Social acceptance; Technology adoption; Thematic analysis; Typology development